Osteointegration of autologous and allogeneic onlay grafts (Research, Society and Development, 2022)
The aim this paper was investigate the biology of incorporation of autologous and allogeneic onlay grafts to mandible of rabbits in association or not with Platelet Rich Plama (PRP). Forty animals composed this experiment. Bones were harvested from the wing of ilium and onlay grafted bilaterally to mandible cortex. Half of the animals received fresh autologous bone and the others received allogeneic bone previously frozen under -70ºC for 120 days. On the right side of the mandible, PRP was added. Euthanasia of the animals took place after 3, 7, 14, 28 and 56 days. Histological sections were stained with hematoxilin and, eosin, toluidin blue, picro-sirius and TRAP. For immunohistochemical study, anti-CD79αcγ, anti-CD3 and anti-RAM11 antibodies were considered. At all variables studied, a superiority on the behavior of allogeneic grafts, especially in the latest periods of grafting was observed. The largest amount of macrophages was detected around allogeneic bones, despite it being the less absorbed. The presence of PRP did not modify the behavior of those variables in a statistically significant way. The frozen allogeneic bone represented a good material for the thickening of the jaw and did not induce immunological reaction. PRP was not effective in improving the healing of onlay bone grafts.